2015
DOI: 10.1103/physrevlett.115.238102
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation Relations of Fitness and Information in Population Dynamics

Abstract: Phenotype-switching with and without sensing environment is a ubiquitous strategy of organisms to survive in fluctuating environment. Fitness of a population of organisms with phenotype-switching may be constrained and restricted by hidden relations as the entropy production in a thermal system with and without sensing and feedback is well-characterized via fluctuation relations (FRs) . In this work, we derive such FRs of fitness together with an underlying information-theoretic structure in selection. By usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…This fluctuation relation depends only on the structure of the branched tree but not on the class of dynamical models defined on it. This relation has analogies with the fluctuation relations well known in Stochastic Thermodynamics [18], as first noted in [19,20], which we further discuss here.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…This fluctuation relation depends only on the structure of the branched tree but not on the class of dynamical models defined on it. This relation has analogies with the fluctuation relations well known in Stochastic Thermodynamics [18], as first noted in [19,20], which we further discuss here.…”
Section: Introductionsupporting
confidence: 72%
“…In this case, the integral of eq. (4.16) is solvable and gives 20) where the Gamma function is defined as…”
Section: Constant Individual Growth Ratementioning
confidence: 99%
“…The corresponding population dynamics has an interesting thermody-namic structure uncovered in Refs. [12,13], which we also exploit here to derive three new fluctuation relations. As usual with fluctuation theorems [14], our results map typical behaviors in one ensemble (here the population level) to atypical behaviors in another one (here the single lineage level).…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical studies have demonstrated the utility of history-based analysis of growing populations, regarding individual histories rather than single cells as the basic replicating entity [2123]. For example, Leibler and Kussell introduced a time-integrated instantaneous reproduction rate, termed historical fitness [21], and defined a measure of selection using the response of mean historical fitness over all histories within a population.…”
Section: Introductionmentioning
confidence: 99%